Utilization of Digital Application as English Learning Media - Maftukh Ghulam Mursyidin; Kinanti Puspita Wahyudi; Majidatun Ahmala (English Education : English Journal for Teaching and Learning, 2022)
The rapid development of 21st century technology forces students to accept various applications and social media platforms as a lifestyle that will become one of the media to show their existence and socialize with peers. The wider reach of the virtual world compared to the real world makes English have very varied functions, such as facilitating communication, capturing target markets/increasing the number of followers, increasing credibility and so on. This study aims to determine the new paradigm that has emerged from various applications and social media platforms that can be used by students to learn English. This study uses a descriptive qualitative method with the aim of analyzing the phenomenon of the existence of various social media applications and platforms used by students in everyday life and making them adapt to the English language in it. This study uses purposive sampling as a method of selecting the object of research, young people aged between 17 and 20, totaling 35 students. Data collection techniques used in this study were interviews with two expert sources and respondents, observation, and documentation. The results of this study indicate that the applications and social media platforms that they often use as media to learn English are: mobile legend game, Spotify music application, Instagram, Netflix, duolingo, cake application, twitter, and tik tok.